2017
DOI: 10.1111/dech.12327
|View full text |Cite
|
Sign up to set email alerts
|

International Allies, Institutional Layering and Power in the Making of Labour in Bangladesh

Abstract: This contribution discusses trajectories of labour power in the making. Taking a practice theory perspective on power, and focusing on the Accord on Fire and Building Safety in Bangladesh, the author asks how Bangladeshi trade unions are attempting to use changes in the industrial landscape after the factory collapse of Rana Plaza in 2013 to constitute different power sources. The article challenges assumptions in power resource theories that associational, institutional and social-cultural power are pre-exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 36 publications
0
55
0
21
Order By: Relevance
“…Countries with weak state capacity lack adequately-staffed labor or health and safety inspectorates (Piore andSchrank 2008, Schrank 2013). Often, host country governments and business owners deny workers the legal or practical rights to form unions and bargain collectively (Ahlquist 2017, Berliner et al 2015, Zajak 2017. The politically privileged position of factory owners therefore allows them to capture many of the gains from global production.…”
Section: Apparel Production and The Private Governance Of Worker Rmentioning
confidence: 99%
“…Countries with weak state capacity lack adequately-staffed labor or health and safety inspectorates (Piore andSchrank 2008, Schrank 2013). Often, host country governments and business owners deny workers the legal or practical rights to form unions and bargain collectively (Ahlquist 2017, Berliner et al 2015, Zajak 2017. The politically privileged position of factory owners therefore allows them to capture many of the gains from global production.…”
Section: Apparel Production and The Private Governance Of Worker Rmentioning
confidence: 99%
“…Traditional sources of power originate from the position of unions in GVCs enabling disruption of production with a strike (structural power) and the ability to organize workers in unions (associational power) (Webster, 2015). Other sources of power are rooted in alliances with NGOs and external support for unions using social movement tactics (societal power) (Zajak, 2017). Bartley and Egels-Zanden (2016) identified a repertoire of union leverage strategies such as calling retailers to support negotiations with local management, using the threat of contacting the retailer if no local solution is found, and using retailer support to build local organizational capacity.…”
Section: Theoretical Background 21 Social Dialogue In Global Value Cmentioning
confidence: 99%
“…This dimension addresses the barriers and hindrances in the environment of workers which reduce the likelihood of their participation. It builds upon my earlier work in which I specify the degree of sensitivity of governance institutions towards local and global power constellations and therefore the ability of powerful actors to block trade unions or social movement organizations from using a certain influence channel (Zajak, a). Workers are deeply embedded in local power relations.…”
Section: Assessing Workers’ Voice In Recursive Governancementioning
confidence: 99%
“…This was also confirmed by a labour rights organization: ‘Typically workers have no clue what the brand is, what the responsibilities of the brand are to them or where they would file the complaint’ (Interview with Hong Kong labour rights organization, 23 April 2009, Hong Kong). In more recent field work in Bangladesh, I found that workers represented by trade unions are much more aware of different transnational complaint procedures if they have stronger ties to the international labour community (Zajak, ). This suggests that the usage of complaint channels depends not only on the availability and transparency of the information, but also on the presence of actors and networks helping workers to make use of them.…”
Section: Comparing Feedback Channels and Workers’ Voicementioning
confidence: 99%